Claudin-7b and Claudin-h are required for controlling cilia morphogenesis in the zebrafish kidney. (March 2020) - Jin, Miaomiao; Wang, Donglian; Xu, Wenyan; Wang, Hong; Cao, Ying
Abstract: Claudins are a family of proteins which are the most important components of the tight junctions. The location of Claudins on the renal tubule epithelial determines its paracellular transport characteristics, but whether Claudins have other functions in kidneys remains still unclear. Here, we showed that the transcripts encoding two Claudin family proteins, claudin-7b ( cldn-7b ) and claudin-h ( cldn-h ), were expressed in the transporting cells in the zebrafish pronephros. By knocking down of cldn-7b and cldn-h in zebrafish, we showed that these claudins morphants exhibited cystic kidneys accompanied with body curvature. Further analysis showed that down regulation of cldn-7b or cldn-h led to multiple defects in apico-basolateral polarity, cilia morphology and ciliary function in kidney. Moreover, the ciliary defect was confirmed by depletion of Cldn-7b or Cldn-h using CRISPR/Cas9 system. We also showed that both cldn-7b and cldn-h were genetically interacted with a well-known ciliary gene, arl13b . Deletion of arl13b led to curly cilia in the pronephros that phenocopied with cldn-7b and cldn-h morphants. Taken together, our data suggested that the tight junction protein, Cldn-7b and Cldn-h, regulate kidney development and function by affecting cilia morphology. Highlights: Cldn-7b and Cldn-h are expressed in transporting epithelia cells in the zebrafish pronephros. Cldn-7b or Cldn-h downregulation causes kidney cyst in zebrafish embryos. Cldn-7b or Cldn-h downregulation causes defective apico-basolateral polarity. Cldn-7b or Cldn-h downregulation leads to curled cilia in zebrafish kidney. Cldn-7b and Cldn-h might act to control cilia morphology in the same way as Arl13b.